Humans created God in their image? An anthropomorphic projectionism in the Old Testament - Mtshiselwa, Ndikho (HTS teologiese studies, 2018)
The Old Testament projects not only a Deity that created the world and human beings but also one that is violent and male. The debate on the depiction of the God of Israel that is violent and male is far from being exhausted in Old Testament studies. Thus, the main question posed in this article is: If re-read as ‘Humans created God in their image’, would Genesis 1:27 account for the portrayal of a Deity that is male and violent? Feuerbach’s idea of anthropomorphic projectionism and Guthrie’s view of religion as anthropomorphism come to mind here. This article therefore examines, firstly, human conceptualisation of a divine being within the framework of the theory of anthropomorphic projectionism. Because many a theologian and philosopher would deny that God is a being at all, we further investigate whether the God of Israel was a theological and social construction during the history of ancient Israel. In the end, we conclude, based on the theory of anthropomorphic projectionism, that the idea that the God of Israel was a theological and social construct accounts for the depiction of a Deity that is male and violent in the Old Testament.